Application of mutant IDH1 antibody to differentiate diffuse glioma from nonneoplastic central nervous system lesions and therapy-induced changes - Capper, David; Sahm, Felix; Hartmann, Christian; Meyermann, Richard; Deimling, Andreas von; Schittenhelm, Jens (The American journal of surgical pathology, 2010)
Differentiation of gliomas and reactive gliosis may be challenging both at primary tumor occurrence and at posttherapy biopsy. The most frequent IDH1 mutation found in the majority of WHO grade II and III gliomas can be visualized with an antibody specifically detecting mutant IDH1R132H protein. In this study, mIDH1R132H immunoreactivity in 120 reactive gliosis specimens of various etiologies is compared with Wilms Tumor 1 (WT1) and p53 expression, both markers applied for the differentiation of reactive gliosis and glioma. Although WT1 and p53 positive glial cells were found in 17% and 63% of cases respectively, all samples were negative for mIDH1R132H. Furthermore, we investigated 19 posttherapy gliomas (6 WHO II, 13 WHO III) with extensive reactive changes and detected mIDH1R132H positive cells in 13 specimens. In 5 of these cases, tumor cells were missed by conventional staining, showing the improved sensitivity of mIDH1R132H. Thus, mIDH1R132H is a tumor-specific marker that is superior to other established markers to differentiate reactive from neoplastic cells in grade II and III gliomas and allows identifying tumor cells in posttherapy specimens with extensive reactive changes. As IDH mutations are not characteristic of grade IV primary glioblastomas, this antibody cannot differentiate primary glioblastoma from reactive gliosis. Thus, caution has to be taken and a combined panel with other markers is needed.